Characterization and applications of Thermomonas hydrothermalis isolated from Jordan's hot springs for biotechnological and medical purposes. (May 2021) - Al-Daghistani, Hala I.; Mohammad, Balsam Talal; Kurniawan, Tonni Agustiono; Singh, Deepak; Rabadi, Alexander D.; Xue, Wenchao; Avtar, Ram; Othman, Mohd Hafiz Dzarfan; Shirazian, Saeed
Graphical abstract: Highlights: Isolated bacteria exhibited an optimum growth at 55 °C, pH 8.5, and 30 min. Basic Local Alignment Search Tool test found 99 % of similarity to T. hydrothermalis . Isolated bacteria exerted cytostimulatory effects on human lung fibroblasts (MRC-5). The same isolate bacteria had an IC50 of 5.109 μg/mL. Abstract: We identified and investigated the biological activities of Thermomonas hydrothermalis, isolated bacteria strains present in Jordan's hot springs, based on their morphological, biochemical, and physiological characteristics. The colonies exhibited light brown with a diameter ranging from 0.5 to 2.0 mm. For screening their metabolic activities, API 50CHB strips and esculin were used. We phylogenetically typified the isolated bacteria by applying 16S ribosomal DNA gene amplification and sequencing followed by the Basic Local Alignment Search Tool (BLAST) tests. About 100 μL of the enriched sample was streaked on nutrient agar using a calibrated wire loop, while 20 μg crude powder was mixed with dimethyl sulfoxide (DMSO) to test their activities against standard pathogenic bacterial strains (ATCC). The water samples collected from the hot springs had temperatures ranging between 44–56 °C, pH between 7.11–8.51, and electrical conductivity between 1.06–1.41 ms/cm. To utilize their isolate for characterization and applications, pH, temperature, and generation time were optimized. It was found that the Gram-negative isolated bacteria strain exhibited an optimum growth at 55 °C, pH 8.5, and 30 min of generation time (GT). The BLAST results showed a 99 % of similar identity of the sample to Thermomonas hydrothermalis . Due to their antibacterial effects against Gram-positive and Gram-negative bacteria, bioactive compounds identified using gas chromatography–mass spectroscopy (GC–MS) had novel features such as 4(3 H)-pyrimidinone, dihydroxy-1, 5- naphthyridine, actinomycine-D, and pyrrolo [1, 2-a]pyrazine-1, 4-dione hygrazides. Screening of cytotoxic activity tests using MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay was conducted toward their water extract, which exerted cytostimulatory effects on human lung fibroblasts (MRC-5) with an IC50 of 5.109 μg/mL and accelerated wound closure. Overall, the implications of this study provided new insights into the bioproducts of Thermomonas hydrothermalis and offered opportunities to utilize their isolate for biotechnological and medicinal applications.